The first record of Caenis Stephens, 1835 in Australia (Ephemeroptera: Caenidae) with descriptions of two new species - Suter, Phillip J.; Mynott, Julia H.; Webb, Jeff M. (Zootaxa, 2023)
Two species of Caenis with straight forceps with a terminal tuft of spines are described from northern Australia. Male imagoes and nymphs of C. hanleyi n. sp. are described from reared material from the Alligator Rivers Region in the Northern Territory and C. binda n. sp. is described only from male imagoes collected from streams in the Wet Tropics of Queensland. C. hanleyi differs from C. binda by the structure of the forceps with C. binda being longer and narrower with longer apical spines. These are the first records of the genus Caenis in Australia.